Financial Illiteracy and Pension Contributions: A Field Experiment on Compound Interest in China - Song, Changcheng (Review of Financial Studies, 2019)
I conduct a field experiment to study the relationship between peoples’ misunderstanding of compound interest and their pension contributions in rural China. I find that explaining the concept of compound interest to subjects increased pension contributions by roughly 40%. The treatment effect is larger for those who underestimate compound interest than for those who overestimate compound interest. Moreover, financial education enables households to partially correct their misunderstanding of compound interest. I structurally estimate the level of misunderstanding of compound interest and conduct a counterfactual welfare analysis: lifetime utility increases by about 10% if subjects’ misunderstanding of compound interest is eliminated.